Typological Assessment of Reconstruction: Did Indo-European Have Inclusive and Exclusive First Person Plural Personal Pronouns? - Shields, Kenneth (Lingua Posnaniensis, 2010)
This brief article attempts to apply current typological theory about the structure of person-marking paradigms to reconstructions of early Indo-European personal pronoun declension and early Indo-European verbal conjugation in order to determine whether or not such application can shed light on the traditional debate about whether or not an inclusive/exclusive opposition can be ascribed to the protolanguage. Despite the demonstrated positive value of typology in assessing the plausibility of reconstructions, the conclusion reached here is that current typological theory is very limited in its ability to resolve this particular issue of historical/comparative Indo-European linguistics.